Structure of microbial communities in Sphagnum peatlands and effect of atmospheric carbon dioxide enrichment - Mitchell, Edward; Gilbert, Daniel; Buttler, Alexandre; Amblard, Christian; Grosvernier, Philippe; Gobat, Jean-Michel (My University, 2003)
Little is known about the structure of microbial communities in Sphagnum peatlands, and the potential effects of the increasing atmospheric CO2 concentration on these communities are not known. We analyzed the structure of microbial communities in five Sphagnum-dominated peatlands across Europe and their response to CO2 enrichment using miniFACE systems. After three growing seasons, Sphagnum samples were analyzed for heterotrophic bacteria, cyanobacteria, microalgae, heterotrophic flagellates, ciliates, testate amoebae, fungi, nematodes, and rotifers. Heterotrophic organisms dominated the microbial communities and together represented 78% to 97% of the total microbial biomass. Testate amoebae dominated the protozoan biomass. A canonical correspondence analysis revealed a significant correlation between the microbial community data and four environmental variables (Na+, DOC, water table depth, and DIN), reflecting continentality, hydrology, and nitrogen deposition gradients. Carbon dioxide enrichment modified the structure of microbial communities, but total microbial biomass was unaffected. The biomass of heterotrophic bacteria increased by 48%, and the biomass of testate amoebae decreased by 13%. These results contrast with the absence of overall effect on methane production or on the vegetation, but are in line with an increased below-ground vascular plant biomass at the same sites. We interpret the increase in bacterial biomass as a response to a CO2-induced enhancement of Sphagnum exudation. The causes for the decrease of testate amoebae are unclear but could indicate a top-down rather than a bottom-up control on their density.
Keywords: TESTATE AMEBAS PROTOZOA; AIR CO2 ENRICHMENT; INCREASED NITROGEN; DEPOSITION; ELEVATED CO2; N-DEPOSITION; BOG VEGETATION; LOLIUM-PERENNE; SOIL PROTOZOA; PLANT; GROWTH